Extraction and Characterization of Naringenin from Psuedohandellia umbelliferae - Lari, Jalil; Vahedi, Hooshang; Bol, Rouhollah (Asian Journal of Chemistry, 2011)
Pseudohandellia umbelliferae collected from Kalat Naderi area, Khorasan Razavi province, Iran was investigated for the presence of naringenin, 5,7-dihydroxy 2-(4-hydroxyphenyl)chroman- 4-one by spectroscopic methods.